Transtornos psiquiátricos e gestação: associação entre parâmetros clínicos e biológicos em uma comunidade rural de baixa renda - Fernando Machado Vilhena Dias (2011)
Background: Psychiatric symptoms during pregnancy induce an increase in morbidity and also in the mortality levels among women and children. Despite the importance of psychiatric disorders during pregnancy, it is still unknow whether pregnancy itself creates a condition that raises the risk of mood disorder development or if it represents a protection factor to the disturbances. So, the literature data is controversial and this question still remains to be solved. There is also a gap in epidemic studies about psychiatric symptoms in pregnant women from the countryside in developing countries. Therefore, studies involving pregnant women who belong to countryside communities can contribute to clarify the particularities of psychiatric manifestations in this group of people, to identify environmental risk factors and to define better public health service for pregnant women. Changes in biological factors such as thiamine (B1 vitamin) and its phosphorylated forms; and cytokines, could have a role in psychiatric disorders and also modify fetal neurodevelopment. However little is known about the involvement of those biological factor changes during pregnancy. Objectives: To assess the occurrence of psychiatric disorders, symptoms and the profile of specific biological factors in pregnant and non-pregnant women from a low income countryside community and also to verify the associations among sociodemographic data, clinical psychiatric and biological parameters. Methods: Ninety-four pregnant women and thirty-eight non-pregnant healthy women assisted at the health service of Conceição do Mato Dentro, a rural low income community in Brazil, with a medium human development index (HDI), participated in the present study. Psychiatric examination included: a structured clinical interview for psychiatric disorders according to Diagnostic Statistical Manual, fourth edition Background: Psychiatric symptoms during pregnancy induce an increase in morbidity and also in the mortality levels among women and children. Despite the importance of psychiatric disorders during pregnancy, it is still unknow whether pregnancy itself creates a condition that raises the risk of mood disorder development or if it represents a protection factor to the disturbances. So, the literature data is controversial and this question still remains to be solved. There is also a gap in epidemic studies about psychiatric symptoms in pregnant women from the countryside in developing countries. Therefore, studies involving pregnant women who belong to countryside communities can contribute to clarify the particularities of psychiatric manifestations in this group of people, to identify environmental risk factors and to define better public health service for pregnant women. Changes in biological factors such as thiamine (B1 vitamin) and its phosphorylated forms; and cytokines, could have a role in psychiatric disorders and also modify fetal neurodevelopment. However little is known about the involvement of those biological factor changes during pregnancy. Objectives: To assess the occurrence of psychiatric disorders, symptoms and the profile of specific biological factors in pregnant and non-pregnant women from a low income countryside community and also to verify the associations among sociodemographic data, clinical psychiatric and biological parameters. Methods: Ninety-four pregnant women and thirty-eight non-pregnant healthy women assisted at the health service of Conceição do Mato Dentro, a rural low income community in Brazil, with a medium human development index (HDI), participated in the present study. Psychiatric examination included: a structured clinical interview for psychiatric disorders according to Diagnostic Statistical Manual, fourth edition related to income per capta,to age at the first pregnancy, to TMP bloodconcentrations and to R1. Conclusions: For this particularcommunity, pregnancy wasassociated with the occurrence of psychiatric disorders, depressive and anxioussymptoms. The present results added to literaturedata, indicate that there are differentcut-off points in the BDI for pregnant women. Socioeconomic factors and TMPdeficiencywere significantlyrelated to the occurrence of psychiatric symptoms. Thechanges observed in the STNFR1, STNFR2 and adiponectine blood levels suggest thatan inflammatory profile might occur in the third trimester of pregnancy.Furtherstudies would be necessary to clarify this phenomenon